Viability and glycosaminoglycan content in chondrocytes transfected with SRY (sex-determining region y)-BOX 9 and telomerase reverse transcriptase genes - Md Nazir, Noorhidayah; Zulkifly, Ahmad Hafiz; Khalid, Kamarul Ariffin; Zainol, Ismail; Zamli, Zaitunnatakhin; Sha'ban, Munirah (2016)
Glycosaminoglycan (GAG) is a major component of cartilage matrix. This essential polysaccharide has the capacity to attract water molecules. Such capacity is important in cartilage primarily because it absorbs shock and provides lubrication in joint. Cartilage degeneration is often a normal ageing change. Along the process, the cartilage cell; chondrocyte may become less viable and thus, downregulate GAG production. This study evaluates cell viability and GAG content in chondrocytes using monolayer culture model. Chondrocyte usually loses its phenotype after several replications in culture. Hypothetically, replicative senescence contributes to ageing indirectly. Hence, this study compares SOX9 and/or TERT transfected and non-transfected chondrocytes to see whether or not the cells could remain viable and produce GAG after serial passages. While SOX9 is essential for chondrogenesis, TERT is responsible for cells longevity. Upon research approval (IIUM/IACUC/Approval/2015/[5]/[24]), rabbits’ articular cartilages (n=2) were harvested. Isolated chondrocytes were seeded in 6 well-plate with an initial seeding of 5,000 cells/cm2. At passage-1, the chondrocytes were transfected with SOX9 and/or TERT genes via lipofection. The four groups namely non-transfected (control), SOX9-, TERT- and SOX9/TERT-transfected chondrocytes were evaluated at passage-1, -2 and -3. It can be appreciated that the post-transfected chondrocytes have cells viability and GAG content comparable to that of the non-transfected group. They exhibited similar downregulation pattern for viability and GAG content as postulated in theory of ageing. The viability ranged from the highest 93.43% to the lowest 78.49% throughout the culture. The total GAG contents are 25.23μg/ml, 23.87μg/ml, 21.59μg/ml and 23.86μg/ml for SOX9-, TERT-, SOX9/TERT-post-transfected chondrocytes and control, respectively. While cells viability gives an indication that transfection may have non-toxic effect on cells, this study raises some significant questions whether or not SOX9 and TERT could maintain or enhance chondrocyte properties at structural and ultrastructural levels. Detailed investigations into molecular and protein levels are also needed.